Defining the Reliability of Deltoid Reanimation by Nerve Transfer When Using Abnormal but Variably Recovered Triceps Donor Nerves - Ferris, Scott; Withers, Aaron; Shukla, Lipi (Frontiers in Surgery, 2021)
Upper brachial plexus injuries to the C5/6 roots or axillary nerve can result in severe deficits in upper limb function. Current techniques to reinnervate the deltoid muscle utilise the well-described transfer of radial nerve branches to triceps to the axillary nerve. However, in around 25% of patients, there is a failure of sufficient deltoid reinnervation. It is unclear in the literature if deltoid reanimation should be attempted with a nerve transfer from a weak but functioning triceps nerve. The authors present the largest series of triceps to axillary nerve transfers for deltoid reanimation in order to answer this clinical question. Seventy-seven consecutive patients of a single surgeon were stratified and analysed in four groups: (1) normal triceps at presentation, (2) abnormal triceps at presentation recovering to clinically normal function preoperatively, (3) abnormal triceps at presentation remaining abnormal preoperatively, and lastly (4) where pre-operative triceps function was deemed insufficient for use, requiring alternative reconstruction for deltoid reanimation. The authors considered deltoid re-animation of ≥ M4 as successful for the purpose of this study. Median Medical Research Council (MRC) values demonstrate group 1 achieves this successfully (M5), while median values for groups 2–4 result in M4 power (albeit with decreasing interquartile ranges). Median post-operative shoulder abduction active range of motion (AROM) values were represented by 170° (85–180) in group 1, 117.5° (97.5–140) in group 2, 90° (35–150) in group 3, and 60° (40–155) in group 4. For both post-operative assessments, subgroup analyses demonstrated statistically significant differences when comparing group 1 with groups 3 and 4 (p < 0.05), while all the other group to group pairwise comparisons did not reach significance. The authors postulated that triceps deficiency can act as a surrogate marker of a more extensive plexus injury and may predict poorer outcomes if the weakness persists representing the trending differences between groups 2 and 3. However, given no statistical differences were demonstrated between groups 3 and 4, the authors conclude that utilising an abnormal triceps nerve that demonstrates sufficient strength and redundancy intraoperatively is preferable to alternative transfers for deltoid reanimation. Lastly, in group 4 patients where triceps nerves are damaged and unusable for nerve transfer, alternative operations can also achieve sufficient outcomes and should be considered for restoration of shoulder abduction.